Mechanical properties and microscopic damage characteristics of coal series limestone under coupling effects of high temperature and impact - Peng Wu; Lianying Zhang; Bing Li; Yadong Zheng; Ming Li; Fuqiang Zhu (Scientific Reports)
Abstract To ensure the safe extraction of deep mineral resources, it is imperative to address the mechanical properties and damage mechanism of coal and rock media under the real-time coupling effect of high temperature and impact. In this study, the impact tests (impact velocities of 6.0–10.0 m/s) on coal-series limestone under real-time high-temperature conditions (25 °C-800 °C) were conducted by the real-time high-temperature split Hopkinson pressure bar (HT-SHPB) testing system, and the microscopic changes in mineral composition under the coupling effect of real-time high-temperature and high strain rate action were investigated by X-ray diffraction (XRD), electron scanning microscopy (SEM), energy dispersive spectroscopy (EDS). The results showed that the dynamic stress-strain curve of coal-series limestone under the real-time coupling effect of high temperature and impact during the compaction stage was not significant; As the impact velocity increases and the temperature increases, the plastic characteristics of the dynamic stress-strain curve become more notable, and the brittle failure of the sample is gradually changed into brittle-ductile failure. Additionally, the dynamic peak stress and dynamic elastic modulus exhibit distinct quadratic variations with the increased temperature, and the dynamic peak stress approximately increases linearly with the impact velocity. The main substances in coal-series limestone are calcite, dolomite, and muscovite. The microscopic morphology of calcite at room temperature is characterized by a thin stepped or layered structure. When the temperature rises to 800 °C, thermal decomposition rarely occurs in calcite, while its physical and mechanical properties undergo alternations. After real-time impact, the degree of crystal fragmentation of calcite increases and a large number of microcracks are generated. The dolomite exhibits a prismatic microscopic morphology at room temperature, characterized by distinct and flat edges, and typically occurs in clusters. When the temperature rises to 600 °C, an increased amount of dolomite initiates thermal decomposition, and the crystal edges become passive, even leading to the granulation phenomenon. Consequently, the impact mechanical properties of limestone are ultimately weakened due to the thermal decomposition of mineral components and changes in physical and mechanical properties caused by high temperature.